ENTRE A MIRAGEM E A UTOPIA: A EFETIVIDADE DO DIREITO HUMANO E FUNDAMENTAL À MORADIA NA CIDADE CAPITALISTA - Stefaniak, João Luiz (2011)
Despite being ensured in the constitutional and infra-constitutional juridical ordainment, the human and fundamental right to housing is far from being fulfilled, since the urban development policy adopted by the Capitalist State is based on its main function that is guaranteeing the production and reproduction of the process of capital accumulation. The urban tools proposed by the City Statute to face property speculation and urban segregation and, consequently induce the reform of the excluding land distribution in Brazilian cities, have not been used by most cities even after ten years of its approval. Housing programs tend to meet the demands of the middle class while the population lower class has no access to banking credit. This scenery reveals contradiction that constitutes the framework of this research: the lack of effectiveness of the right to housing in the city despite its existence in the urban legislation. From the conceptualization of decent housing and the right to housing, this paper highlights the protagonist role of the Capitalist State and the urban social movement regarding housing as a social issue, it also analyses the interlink between housing, the right to housing and the similar categories city and the right to a sustainable city. Taking into consideration the uneven and combined development of the capitalist urbanization process – will focus on the urban phenomenon called slums which constituted the city, necessary object of regularization and land urbanization. The city of Ponta Grossa was chosen for the practical observation of the hypothesis formulated, and its urban municipal legislation as well as the local urban social movement were analyzed. It was concluded that the contradiction between urban norm and urban policy employed by the municipality, which implies the lack of universality of the right to decent housing, is associated to the current phase of capitalist development, characterized by the system structural crisis. This reality is partially hidden by the ideological mirage articulated by the Capitalist State, and a task is posed to the urban social movement: the construction of the social city utopia and a sustainable environment on the ruins of such a mirage.